PENGARUH METODE PEMBAYARAN DALAM MERGER DAN AKUISISI TERHADAP ABNORMAL RETURN SAHAM YANG LISTED DI BEI - Shella Kriekhof (AkMen JURNAL ILMIAH, 2016)
This study bertujuanUntuk know the effect of the announcement of M & A to abnormal return acquirer's shareholders as cash and shares used as payment M & A; as well as to determine the difference between the abnormal return of M & A, which is repaid using the cash to M & A, which is repaid using shares. While the methods of analysis used in this research is event study. Event study used for empirical research on the relationship between the price of the securities to the events of this ekonomi.Studi studying the stock market reaction to an event that information is published as an announcement. The results of this study indicate the cash payment method likely to generate positive abnormal return for the company. While the method of payment of shares likely to cause companies to obtain negative abnormal return. From the statistical test showed that there is no difference of abnormal return based on the method of payment of cash and shares in companies that carry out mergers and acquisitions. These results indicate that although the cash payment methods are more likely to give a positive abnormal return than the stock payment method, but the test results are not strong enough to show the influence of the abnormal return payment method companies.